Efektivitas Program E-TLE Dalam Menangani Pelanggaran Lalu Lintas di Kota Surabaya - Aldi Kurnia Wahyu; Tukiman Tukiman (Universitas Mataram, 2022)
Electronic Traffic Law Enforcement (E-TLE) has the coverage of several traffic violation systems, including traffic accidents, traffic violations, traffic crimes, and others. E-TLE is the digitization of the ticketing process based on Law Number 22 of 2009 concerning road traffic and transportation and Government Regulation Number 80 of 2012 concerning Procedures for Inspection of Motorized Vehicles. The E-TLE system is considered not to be able to run optimally due to various factors, one of which is the heterogeneous quality of recording accuracy. Thus the purpose of this study is to determine the effectiveness of the E-TLE program in dealing with traffic violations in the city of Surabaya. This study used descriptive qualitative method. The results of the study show that the effectiveness of the E-TLE program can be seen from 4 indicators, namely 1) the accuracy of the program targets is considered correct even though it has not been maximized by using the data obtained from informants as guidelines, 2) the program socialization has not been evenly distributed and is characterized by public ignorance regarding the existence of the program. the program, 3) the program's objectives are still not in line with the community because the impact of cctv supervision causes the weakness of direct criminal activity, 4) program monitoring carried out by the police is still not contributing so that the number of traffic violations increases.